Excess direct hospital cost of treating adult patients with ventilator associated respiratory infection (VARI) in Vietnam - Dat, V; Huong, V; Turner, H; Thwaites, L; Van Doorn, H; Nadjm, B (Public Library of Science, 2018)
Introduction Ventilator associated respiratory infections (VARIs) are the most common hospital acquired infections in critical care worldwide. This work aims to estimate the total annual direct hospital cost of treating VARI throughout Vietnam. Methods A costing model was constructed to evaluate the excess cost of diagnostics and treatment of VARI in Vietnam. Model inputs included costs for extra lengths of stay, diagnostics, VARI incidence, utilisation of ventilators and antibiotic therapy. Results With the current VARI incidence rate of 21.7 episodes per 1000 ventilation-days, we estimated 34,428 VARI episodes in the 577 critical care units in Vietnam per year. The extra cost per VARI episode was $1,174.90 and the total annual excess cost was US$40.4 million. A 1% absolute reduction in VARI incidence density would save US$1.86 million annually. For each episode of VARI, the share of excess cost components was 45.1% for critical care unit stay and ventilation, 3.7% for diagnostics and 51.1% for extra antimicrobial treatment. Conclusions At the current annual government health expenditure of US$117 per capita, VARI represents a substantial cost to the health service in Vietnam. Enhanced infection prevention and control and antimicrobial stewardship programmes should be implemented to reduce this.